Pengaruh Penambahan Bungkil Inti Sawit Fermentasi Dengan Lama Waktu Berbeda Terhadap Konversi Pakan dan Pertumbuhan Ikan Kelabau (Osteochilus melanopleurus) - Maria Damanik; Heru Kusdianto; Esti Handayani Hardi; Henny Pagoray; Isriansyah Isriansyah (Jurnal Akuakultur Sungai dan Danau, 2023)
Kelabau (Osteochilus melanopleurus) is one of the local fish found in Borneo. Economically, kelabau fish has a reason to be cultivated because it has a fairly high price. One of the aspects that needs to be considered is the availability of raw materials. This study aimed to evaluate the use of fermented palm kernel meal in feed on feed conversion, growth, and survival of kelabau. The experimental design applied was a Completely randomized design (CRD) with 4 treatments and 3 replicates, namely (P0) no palm kernel meal added; (P2) palm kernel meal fermented for 0 hours, (P3) palm kernel meal fermentaded for 24 hours, and (P4) palm kernel meal fermented for 48 hours. Fish rearing was carried out for 40 days with feeding experimental frequency three times a day with at satiation. The  fish  was  kelabau  seeds measuring 4-5 cm and weighing 1-2 g. Ovserved variades tested in this study included feed conversion rasio , growth, and survival rate. The highest growth was resulted by  palm kernel meal fermented for 48 hours, the lowest feed conversion ratio (FCR) was resulted by falm kernel meal fermented 24 hours, and the survival of all treatment during this rearing werw 100%. However statisticaly no significant differences were observed in either/ grow or feed conversion ratio.  Kata kunci: Kelabau; EM4;  fermentasi; bungkil inti sawit